Serum uric acid level and subclinical left ventricular dysfunction: a community‐based cohort study - Koki Nakanishi; Masao Daimon; Yuriko Yoshida; Jumpei Ishiwata; Naoko Sawada; Megumi Hirokawa; Hidehiro Kaneko; Tomoko Nakao; Yoshiko Mizuno; Hiroyuki Morita; Marco R. Di Tullio; Shunichi Homma; et al. (ESC Heart Failure)
Abstract Aims Although serum uric acid (SUA) level is correlated with oxidative stress and serves as a marker of poor prognosis in heart failure patients, its possible association with subclinical left ventricular (LV) dysfunction has not been evaluated. This study aimed to investigate the association between SUA and subclinical LV dysfunction in a sample of a general population without overt cardiac disease. Methods and results We examined 1175 participants who underwent extensive cardiovascular health check‐up including laboratory tests and speckle‐tracking echocardiography to assess LV global longitudinal strain (GLS). The association of SUA concentration, as a continuous variable and a categorical variable using quartiles, with the presence of abnormal LVGLS was assessed. Mean age was 62 ± 12 years, and 656 (56%) were male participants. Mean SUA was 5.6 ± 1.3 mg/dL (25th–75th percentile, 4.6–6.5 mg/dL). The prevalence of abnormal LVGLS (greater than –18.6%) was greatest in the upper quartile of SUA. In multivariable analysis, SUA as a continuous variable was significantly associated with abnormal LVGLS [adjusted odds ratio (OR), 1.26 per 1 mg/dL; P = 0.008] independent of traditional cardiovascular risk factors, pertinent laboratory parameters and echocardiographic measures, and medications. In the categorical analysis, the upper quartile of SUA was independently associated with abnormal LVGLS in a fully adjusted model (adjusted OR, 2.28 vs. lowest quartile; P = 0.020). Conclusions In a sample of the general population, an elevated SUA was independently associated with subclinical LV dysfunction. Assessment of LVGLS may add important prognostic information in individuals with elevated SUA, even in the absence of overt cardiac disease.